Early childhood obesity and subsequent asthma diagnoses: A longitudinal study using linked routinely collected data from Wales - Abdeldayem, Waleed; Davies, Jo; Griffiths, Lucy (International Journal of Population Data Science, 2024)
Introduction Obesity and asthma are two of the most common childhood conditions and their prevalence have increased over the last decades. Several cross-sectional studies provide strong evidence for a positive association between these two conditions. However, few longitudinal studies have examined the temporal relationship between them. Objective To examine the relationship between body mass index (BMI) at school starting age and the risk of developing bronchial asthma later in childhood. Methods We used anthropometric measurements of children aged 4 to 5 years, obtained as part of a national surveillance programme in Wales, linked to multiple population-level longitudinal administrative and clinical datasets within a trusted research environment provided by the Secure Anonymised Information Linkage (SAIL) Databank. We examined whether obesity at age 4 to 5 years was associated with increased risk of having a recorded diagnosis of asthma during a nine year follow-up period using logistic regression analysis. Results Out of 22,790 children included in the study, 7% had a recorded diagnosis of asthma during the nine years following their anthropometric measurement. Children with obesity (Body Mass Index [BMI] Z-score ≥98th Centile) had a 41% increased risk of having a recorded diagnosis of asthma (adjusted odds ratio [aOR]: 1.41; 95% confidence interval [CI]: 1.17-1.7). Females were 26% less likely to have a recorded diagnosis of asthma after adjusting for weight status and deprivation index (aOR: 0.74; 95% CI: 0.67-0.82). Conclusion Obesity in children aged 4 to 5 years carries an increased risk of developing asthma. Anthropometric measurements obtained through standardised population-level surveillance programmes enable important research that would otherwise be impossible. Expanding these programs to include older age groups is recommended. Additionally, lifestyle interventions aimed at weight loss may help reduce the risk of developing asthma.